PERCEIVED CHALLENGES SOCIAL WORKERS EXPERIENCE IN PROVIDING DEINSTITUTIONALISED SERVICES TO MENTAL HEALTH CARE USERS - Webb, Portia; Adlem, Anri Gretha (Social Work/Maatskaplike Werk, 2025)
Mental, physical and social health are vital, interdependent strands of life for all individuals. Unfortunately, in most parts of the world mental health and mental disorders are not regarded with the same importance as physical health, and are consequently largely ignored or neglected. This article aims to understand the challenges encountered by social workers in mental health care. The phenomenological design, supported by the exploratory, descriptive, contextual and case study designs, was utilised to answer the research question. Ten purposely selected social workers were interviewed by using semi-structured interviews. Thematic analysis following Tesch’s model was applied. The trustworthiness of the study was ensured. Ethical principles were adhered to. The findings of this study indicated that most social workers in mental healthcare are not adequately trained and, similarly, social workers bear the burden of educating mental health care users, their families and the community at large on mental health. Authorities and policymakers need to craft customised, effective and efficient care for mental health care users.